Contact Languages: Ecology and Evolution in Asia - Ansaldo, Umberto (Cambridge University Press, 2009)
Why do groups of speakers in certain times and places come up with new varieties of languages? What are the social settings that determine whether a mixed language, a pidgin or a Creole will develop, and how can we understand the ways in which different languages contribute to the new grammar? Through the study of Malay contact varieties such as Baba Malay, Cocos Malay and Sri Lanka Malay, as well as the Asian Portuguese vernacular of Macau, and China Coast Pidgin, this book explores the social and structural dynamics that underlie the fascinating phenomenon of the creation of new, or restructured, grammars. It emphasizes the importance and interplay of historical documentation, socio-cultural observation and linguistic analysis in the study of contact languages, offering an evolutionary framework for the study of contact language formation - including pidgins and Creoles - in which historical, socio-cultural and typological observations come together.